Self-mentions and Attitude Markers in Turkish Research Article Abstracts - Buse Şen Erdoğan (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Metadiscourse markers are analyzed in many different languages in detail. This study focuses on two interactional metadiscourse markers: attitude markers and self-mentions in Turkish RA abstracts. In the study, two different scientific area, namely social sciences and natural sciences are compared regarding the use of attitude markers and self-mentions in RA abstracts. There are two questions to answer. The first one is related to the features of abstracts defined in the literature. Since RA abstracts are defined as an objective summery of an article, it is expected not to encounter attitude markers and self-mentions frequently. Because these two markers have the two main functions of reflecting the writer’s attitude towards the topic of the study and to adjust the level of intimacy with the reader. Thus, this study questions whether RA abstracts are like how they are defined in terms of objectivity. Also, it searches whether there is any difference between social sciences and natural sciences related to the use of attitude markers and self-mentions. It is found that Turkish abstracts generally protect their objective stance by avoiding especially self-mentions. However, it is also discovered that social sciences show a more flexible attitude in this regard and use more attitude markers and self-mentions compared to natural sciences.